Reputation of Terror Groups Dataset: Measuring popularity of terror groups. (March 2016) - Tokdemir, Efe; Akcinaroglu, Seden
Violence against civilians is not the only tool among the arsenal of terrorists; it is only one of many. Up until now, there did not exist any quantitative data on the different strategies adopted by terror groups that measured the group's popularity or its public support. The Reputation of Terror Groups dataset (RTG) addresses this void. To understand which terror groups build different types of reputation, to analyze the consequences of reputation building and how reputation changes with and influences conflict dynamics, we need to be able to measure the loaded concept of reputation. RTG is the first systematic measure for the reputation of terror groups across countries or time. The dataset includes 443 terror groups operating across 31 years, which makes a total of 2, 641 observations. The large sample size of the RTG dataset allows comparisons of popularity among groups. Additionally, the dataset adopts a multivariable approach by examining multiple aspects of both positive and negative reputation building. Another novelty of the dataset is its measure of reputation with regard to each target, mainly its constituency and target audience. The RTG data can help us come up with new and novel ways of understanding terror groups, and contribute to bridging the gap between micro- and mezzo-level studies in the literature by showing how terror groups adopt different strategies in their constituency and target audience to pursue their goals. In this article, we give an overview assessment of the RTG dataset, display some interesting trends in the data, and explain the data collection procedure, its challenges, and its limitations.